Ultra-High Dilutions and Homeopathy: Can They Be Explained without Non-Local Theory? - Almirantis, Yannis; Tsitinidis, Konstantinos (Homeopathy, 2018)
We discuss questions related to the ‘Benveniste Affair’, its consequences and broader issues in an attempt to understand homeopathy. Specifically, we address the following points:1. The relationship between the experiments conducted by Benveniste, Montagnier, their collaborators and groups that independently tested their results, and ‘traditional’ homeopathy.2. Possible non-local components such as ‘generalised entanglement’ as the basis of the homeopathic phenomenon and experimental evidence for them.3. The capability of highly diluted homeopathic remedies to provoke tangible biological changes in whole organisms and cellular experimental systems.4. Aspects of the similia principle related to the above.5. Suggestions that can lead to experimental verifications of the non-local hypothesis in homeopathy.
Keywords: homeopathy; memory of water; potentised ultra-diluted remedies; Benveniste's experiment; non-locality; generalised entanglement; causality; similia principle